Numerical Modeling of Heat Transfer in Gun Barrel with Experimental Validation - Alan Suyadnya, Kadek; Tarwidi, Dede; Budi Setiawan, Erwin; Febrian Umbara, Rian (International Journal of Engineering and Technology, 2019)
Transient heat transfer in a gun barrel has been investigated numerically in this paper. Numerical modeling is conducted with the objective to obtain temperature history of the gun barrel. From the temperature history, the maximum number of gun shots before the cook-off temperature of the gun barrel attained can be known. Gun barrel is a part of firearm functioned to control gas flow which is aimed to propel projectiles out of the barrel with high velocity. Each propelled projectile produces very high temperature caused by projectiles explosion and friction between projectiles and bore surface. If the temperature of the gun barrel reaches the cook-off temperature, the bore surface will be damaged. Heat conduction equation in cylindrical domain is used to model heat transfer inside the gun barrel. Numerical results are obtained by implementing the finite volume method. From the numerical simulations, we found that our numerical method has very small error compared to experimental data that are 1.68% and 0.95% for total heat transfer and maximum temperature of bore surface, respectively. Moreover, the maximum number of gun shots in order not to attain the cook-off temperature is 27 times with ten seconds per shot and rest time six seconds in every six gun shots.Â Â